Sandy aquifer collapse mechanism and accident treatment of the Qingdao metro tunnel - Zhang, Liwei; Wang, Zaiquan; Zhang, Weiguo; Liu, Sijia (Frontiers in Earth Science, 2023)
The tunnel collapse occurred during the construction of the Qingdao Metro Line Ⅰ, resulting in a pit measuring approximately 10m in diameter and 7m in depth on the ground surface.The collapse inflicted substantial economic losses, casualties, and subsequent disruptions to ongoing construction activities. To clarify the causes of this collapse and investigate the underlying factors, a comprehensive approach combining field surveys and numerical simulations was undertaken. The results show that the collapse was primarily attributed to inadequate support when facing the challenging geological conditions, poor surrounding rocks (Grade VI) and a high volume of groundwater. The combination of abundant water and sand seeped into the tunnel, culminating in a catastrophic ground collapse. Notably, the arch roof experienced extensive deformation and damage due to the significant seepage pressure, which was exacerbated by the absence of timely support.Then, ground grouting was promptly conducted to repair the affected area and reinforce the tunnel structure. Subsequent monitoring of surface deformations following the resumption of tunneling operations indicated the effectiveness of the disaster treatment approach. These achievements constitute a reliable theoretical foundation for similar projects, particularly in terms of environmental protection and ensuring safe construction practices.